Contamination with eggs of Toxocara spp in public parks of La Molina district, Lima, and its relationship with the sanitary surveillance program of parks and gardens - Malca V., Carlos (2019)
The aim of this study was to determine the contamination of public parks of La Molina district in Lima with eggs of Toxocara spp and its relationship with the categorization of the parks (unfriendly, friendly and not very friendly) within the Health Surveillance Programme of Parks and Gardens, prepared by the Department of Food Hygiene and Zoonoses of DIGESA - Ministry of Health (MINSA). The study was of descriptive type, evaluating 131 public parks between August 2014 and April 2016. Representative samples of soil and grass (1-2 kg) per park were collected using the double W technique and analysed by the techniques of sedimentation and flotation with supersaturated NaCl solution. The presence of at least one Toxocara spp egg in the sample was considered positive. The categorization of the parks was carried out by La Molina Municipality staff, based on three criteria (adequate infrastructure, environment and sanitary risks) according to the "Environmental Sanitary Assessment Card for Parks and Gardens" of DIGESA-MINSA. Only one park was positive, representing a prevalence of 0.76%. In parallel, five parks were considered unfriendly, 75 as friendly and 51 as not very friendly, where the positive park was a not very friendly one. It was not possible to relate both results due to the small number of positive parks. The low percentage of contaminated parks was probably due to the implementation by the municipality of the Sanitary Vigilance Programme of Parks and Gardens (responsible tenure, excreta collection, etc.), as well as the constant improvements made since 2011 and the frequent deworming campaigns and informative talks to pet owners.